Uma proposta de protocolo colaborativo e seguro para nuvens de armazenamento de dados - LIMA, Hugo Brito (2020)
Cloud storage services allow a collaborative environment in which users can share files between themselves. For that, users usually specify which files can be shared and which users can access those files. Silva et al. (2014) introduced an idea that does not require a previous statement specifying who may have access to those shared files. The protocol of Silva et al. (2014) allows users to share data automatically by means of their similar interests. As a result, users do not need to know any information about other users, such as email addresses, before sharing. However, the security of stored data was not approached in the scheme provided and in this present work it is proposed a new collaborative protocol that successfully secure data in the cloud, while it still maintains key-features from the previous protocol. This will be attained by the use of secure techniques, widely used in the literature, aiming at securing user’s data.